Perioperative changes in nutritional parameters and impact of graft size in patients undergoing adult living donor liver transplantation. Issue 12 (December 2014) - Hammad, Ahmed; Kaido, Toshimi; Ogawa, Kohei; Fujimoto, Yasuhiro; Tomiyama, Koji; Mori, Akira; Uemura, Tadahiro; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> Derangements of various serum biochemical nutritional/metabolic parameters are common in patients with end‐stage liver disease who undergo liver transplantation (LT). The aim of this study was to explain the benefit of LT with respect to parameter changes and to examine the impact of the graft‐to‐recipient weight ratio (GRWR) on such changes. We investigated each parameter's course in 208 adult recipients for 1 year after living donor LT and analyzed changes in the parameters with a GRWR of 0.8% as the cutoff point. Bonferroni corrections were applied to account for multiple testing. Liver disease–induced high pretransplant ammonia and tyrosine levels and low branched‐chain amino acids to tyrosine ratio (BTR) and zinc levels normalized within 2 weeks after transplantation, and the total lymphocyte count (TLC) normalized within 2 months, whereas low pretransplant prealbumin levels took 1 year to normalize. Branched‐chain amino acids (BCAA), zinc, and TLC levels transiently dropped shortly after transplantation and then were corrected later. An accelerated recovery of ammonia and tyrosine levels and the BTR were found with larger grafts, especially early after transplantation, whereas zinc, prealbumin, BCAA, and TLC levels recovered regardless of the graft size. In conclusion, graft size had little effect on the recovery of nutritional/metabolic parameters except for ammonia and tyrosine levels. Liver Transpl 20:1486‐1496, 2014. © 2014 AASLD.